The Importance of Home Cleaning: Sediment Transport by Alpheid Shrimps Provides a Competitive Advantage to Their Host Anemones - Pérez-Botello, Antar Mijail; Mascaró, Maite; Simões, Nuno (Frontiers in Marine Science, 2021)
Bartholomea annulata is a facultative host of the A. armatus species complex. In the Mexican Caribbean it is commonly found in cracks and crevices located where the vertical walls meet the sandy bottom or on large coral patches away from the sand. To protect themselves from predators, anemones often contract their hydraulic body into a cavernous den and extend the stinging tentacles towards the entrance. The high sediment dynamics of the region, however, result in a permanent risk of animal shelters to be obstructed by sand. By both analysing field data and conducting laboratory experiments with artificial shelters, the present study explored the den cleaning behaviour widely extended amongst alpheid shrimp, and its role in the alpheid-anemone symbiotic interaction. Videorecordings showed that den cleaning was composed of three main behaviours: digging, tossing and tamping. It commenced as soon as 7.2 ± 10.5 minutes after anemones were recognised by alpheids, and behaviours were displayed systematically amongst all 12 replicates. Despite being completely burrowed in sand, Alpheus spp were capable of finding the anemone and liberating the entrance of the artificial shelters in less than 2.5 hours. In addition, manipulative experiments showed that anemones confronted with shelters that were obstructed with sediment had a 25% probability of fully retracting when Alpheus spp. were absent, compared to a 75% probability when shrimps had cleaned the shelter´s entry and internal passage. The analysis of field data indicated that the presence of alpheid shrimps as symbionts of B. annulata was 30% higher amongst anemones in close contact with sandy bottoms than when inhabiting crevices on the top or lateral walls of hard substrates, away from the sediment. Overall, our study concludes that den cleaning constitutes a quick and effective mechanism to assure the anemone’s full retraction into their den, and by keeping the sediment away, alpheids provide the necessary conditions that serve both the anemone´s and the shrimp´s higher chances of acquiring maximum protection from predators. This advantageous exchange in protection partially explains why alpheids are more frequently present in B. annulata in interface microhabitats where the benefit of the interaction is maximized.